Metagenomic insights into the development of microbial communities of straw and leaf composts - Kimeklis, Anastasiia K.; Gladkov, Grigory V.; Orlova, Olga V.; Lisina, Tatiana O.; Afonin, Alexey M.; Aksenova, Tatiana S.; Kichko, Arina A.; Lapidus, Alla L.; Abakumov, Evgeny V.; Andronov, Evgeny E. (Frontiers in Microbiology, 2025)
IntroductionSoil microbiome is a major source of physiologically active microorganisms, which can be potentially mobilized by adding various nutrients. To study this process, a long-term experiment was conducted on the decomposition of oat straw and leaf litter using soil as a microbial inoculum.MethodsCombined analyses of enzymatic activity and NGS data for 16S rRNA gene amplicon and full metagenome sequencing were applied to study taxonomic, carbohydrate-active enzyme (CAZy), and polysaccharide utilization loci (PULs) composition of microbial communities at different stages of decomposition between substrates.ResultsIn straw degradation, the microbial community demonstrated higher amylase, protease, catalase, and cellulase activities, while peroxidase, invertase, and polyphenol oxidase were more active in leaf litter. Consistent with this, the metagenome analysis showed that the microbiome of straw compost was enriched in genes for metabolic pathways of simpler compounds. At the same time, there were more genes for aromatic compound degradation pathways in leaf litter compost. We identified nine metagenome-assembled genomes (MAGs) as the most promising prokaryotic decomposers due to their abnormally high quantity of PULs for their genome sizes, which were confirmed by 16S rRNA gene amplicon sequencing to constitute the bulk of the community at all stages of substrate degradation. MAGs from Bacteroidota (Chitinophaga and Ohtaekwangia) and Actinomycetota (Streptomyces) were found in both composts, while those from Bacillota (Pristimantibacillus) were specific for leaf litter. The most frequently identified PULs were specialized on xylans and pectins, but not cellulose, suggesting that PUL databases may be underrepresented in clusters for complex substrates.DiscussionOur study explores microbial communities from natural ecosystems, such as soil and lignocellulosic waste, which are capable of decomposing lignocellulosic substrates. Using a comprehensive approach with chemical analyses of the substrates, amplicon, and full metagenome sequencing data, we have shown that such communities may be a source of identifying the highly effective decomposing species with novel PULs.